1969
DOI: 10.1039/j39690000298
|View full text |Cite
|
Sign up to set email alerts
|

A total synthesis of isoliensinine

Abstract: t I n this case suffix ' a ' means the corresponding optically active compounds, and this sign is used in the following coinpounds.Chao Tse-yuan, Chou Yun-lee, Young Tao-tsin, and Chou Tsenquo, Scientica Sinica, 1962, 11, 215.2 Pan Pei-chuan, Chou Yun-lee, Sun Tsun-tsi, and Yee-sheng,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In 1969, Karnetani et al reported the chemical synthesis route of isoliensinine (Kametani et al, 1969; Supplementary Figure S2A). Cyclization of amide 3) obtained by condensation of 4benzyloxy-3-methoxyphenethylamine 1) and 4methoxyphenylacetic acid 2) at 180-190°C underwent a Bischler-Napieralski reaction to yield 3,4-dihydroisoquinoline (4), which further gave rise to 4′-O-methyl-N-methylcoclaurine 7) through multiple reactions (5,6).…”
Section: Chemosynthesis and Biosynthesismentioning
confidence: 99%
“…In 1969, Karnetani et al reported the chemical synthesis route of isoliensinine (Kametani et al, 1969; Supplementary Figure S2A). Cyclization of amide 3) obtained by condensation of 4benzyloxy-3-methoxyphenethylamine 1) and 4methoxyphenylacetic acid 2) at 180-190°C underwent a Bischler-Napieralski reaction to yield 3,4-dihydroisoquinoline (4), which further gave rise to 4′-O-methyl-N-methylcoclaurine 7) through multiple reactions (5,6).…”
Section: Chemosynthesis and Biosynthesismentioning
confidence: 99%
“…Coclaurine ( 1a ) and its O- benzylated and/or O- methylated derivatives were prepared by the classical Bischler−Napieralski 3,4-dihydroisoquinoline synthesis and subsequent reduction of the intermediates with NaBH 4 , followed in most cases by N- alkylation. N- Methylation was best carried out with aqueous formaldehyde and NaBH 4 , ,, and N- ethylation and N- propylation were performed by treating the secondary amines with ethyl iodide or propyl bromide in acetonitrile containing NaHCO 3 , respectively. 12- O- Benzylcoclaurine ( 9a ) was prepared conveniently by selective debenzylation of 7,12- O,O ‘ -dibenzylcoclaurine ( 6a ) with SnCl 4 …”
mentioning
confidence: 99%
“…From the viewpoint of the structure-activity relationship, we synthesized three stereoisomers of neferine and O-methylneferine, 5,13,14) and examined these pharmacological activities.…”
mentioning
confidence: 99%